Pendampingan Suami pada Ibu Bersalin Berhubungan dengan Keberhasilan Inisiasi Menyusu Dini - Fitriana Fitriana (JNKI (Jurnal Ners dan Kebidanan Indonesia) (Indonesian Journal of Nursing and Midwifery), 2017)
Early Initiation of Breastfeeding is important for newborns to prevent high neonatal mortality. Early Initiation of Breastfeeding Is where a baby searchs for Mother’s nipple immediately after birth. This study aimed to analyze The relationship between husband assistance in maternity and the success of early initiation of breastfeeding. This study Is a quantitative research, analytical observational study with cross-sectional design. The sampling technique used total sampling. Sample was a total of 39 women whose delivery in private midwife clinics. DepokSleman while The data collection used questionnaire and observation sheets The result from logistic regression showed that husband assistance was significantly associated with early initiation of breastfeeding (OR=3.46; CI95%=1.44 to 6.00; P=0.014) husband assistance on maternity women may increase the success of maternity women to breastfeed their babies as early as possible.